On being a teacher : the human dimension - Kottler, Jeffrey A.; Zehm, Stanley j. (Thousand Oaks, Calif. : Corwin Press, 2000)
Updated Edition of BestsellerThis updated best-seller explores the human resources teachers need in order to gain attention, respect, and devotion from their students.
Includes bibliographical references and index.
Keywords: Teaching; Motivation in education; Teachers